Influence of Laser Ablation Treatment on Electrochemical Characteristics of AZ80 Magnesium Alloy - Daniel Kajánek; Luboš Halimovič; Martina Jacková; Leoš Doskočil; Ingrid Zuziaková; Branislav Hadzima (Communications, 2025)
In this study was investigated the effect of a novel surface treatment technique, called laser ablation or laser surface cleaning (LSC), on the electrochemical properties of AZ80 magnesium alloys. Its effect on corrosion resistance was compared to conventional techniques represented by grinding and polishing. The corrosion stability of the produced surfaces was determined by potentiodynamic (PD) polarization tests and electrochemical impedance spectroscopy in 0.1M NaCl. The results showed that the LSC process produced a regular, uniform surface morphology. Although the LSC treatment led to the passivation of the AZ80 surface, the overall corrosion resistance was compromised compared to surfaces treated by grinding and polishing.